Impact of Macroeconomic Factors and Firm Characteristics on Stock Returns in Nepalese Insurance Companies - Shakya, Leesa (Nepalese Journal of Economics, 2024)
This study examines the impact of macroeconomic factors and firm characteristics on the stock returns in Nepalese insurance companies. Market price per share and stock return are the selected dependent variables. The selected independent variables are inflation rate, money supply, GDP growth, total assets, firm age and net earned premium. The study is based on secondary data of 15 insurance companies with 105 observations for the study period from 2016/17 to 2022/23. The data were collected from the annual audited financial statements and website of respective insurance companies. The correlation coefficients and regression models are estimated to test the significance and importance of macroeconomic factors and firm characteristics on the stock returns in the context of Nepalese insurance companies. The study showed that inflation has a negative effect on market price per share and stock return. It implies that increase in inflation rate leads to decrease in market price per share and stock return. Similarly, money supply has a positive effect on market price per share and stock return. It means that increase in money supply leads to increase in market price per share and stock return. Likewise, GDP growth rate has a positive effect on market price per share. It indicates that increase in GDP growth rate leads to increase in market price per share. In contrast, total assets have a negative effect on market price per share and stock return. It indicates that increase in total assets leads to decrease in market price per share and stock return. In addition, firm age has a negative effect on market price per share and stock return. It implies that increase in firm age leads to decrease in market price per share and stock return. Moreover, net earned premium has a negative effect on market price per share and stock return. It means that higher the net earned premium, lower would be the market price per share and stock return.